Efficacy and Safety of AVP-21D9, an Anthrax Monoclonal Antibody, in Animal Models and Humans - Malkevich, Nina V. (American Society for Microbiology, 2014)
Anthrax is an acute infectious disease caused by the spore-forming bacterium Bacillus anthracis. Timely administration of antibiotics approved for the treatment of anthrax disease may prevent associated morbidity and mortality. However, any delay in initiating antimicrobial therapy may result in increased mortality, as inhalational anthrax progresses rapidly to the toxemic phase of disease. An anthrax antitoxin, AVP-21D9, also known as Thravixa (fully human anthrax monoclonal antibody), is being developed as a therapeutic agent against anthrax toxemia. The efficacy of AVP-21D9 in B. anthracis-infected New Zealand White rabbits and in cynomolgus macaques was evaluated, and its safety and pharmacokinetics were assessed in healthy human volunteers. The estimated mean elimination half-life values of AVP-21D9 in surviving anthrax-challenged rabbits and nonhuman primates (NHPs) ranged from approximately 2 to 4 days and 6 to 11 days, respectively. In healthy humans, the mean elimination half-life was in the range of 20 to 27 days. Dose proportionality was observed for the maximum serum concentration (C(max)) of AVP-21D9 and the area under the concentration-time curve (AUC). In therapeutic efficacy animal models, treatment with AVP-21D9 resulted in survival of up to 92% of the rabbits and up to 67% of the macaques. Single infusions of AVP-21D9 were well tolerated in healthy adult volunteers across all doses evaluated, and no serious adverse events were reported. (This study has been registered at ClinicalTrials.gov under registration no. NCT01202695.)